Music as a perioperative, non-pharmacological intervention in veterinary medicine. Establishing a feasible framework for music implementation and future perspectives with a focus on the perioperative period of dogs and cats - Georgiou, Stefanos G.; Galatos, Apostolos D. (Frontiers in Veterinary Science, 2025)
Research in human medicine has provided sufficient evidence to support music’s incorporation into the perioperative period, suggesting it as a significant non-pharmacological adjunct in terms of a multimodal approach, which should be available to all surgical patients. The literature regarding music’s effect on the perioperative period of dogs and cats is far more limited compared to that of humans, albeit quite promising. In order to design an individualized and potentially successful music intervention in dogs and cats, a stepwise approach is proposed taking into consideration the recommended components, such as music type (genre, tempo, pitch, instrumentation), volume, method of music delivery, duration and timing of the music intervention, frequency of music presentation and the effect of previous music experience. This review aims to provide directions to standardize perioperative music intervention protocols in dogs and cats, incorporate them into clinical practice and propose future perspectives, based on the existing literature evidence both in humans and companion animals.